Iowa Ornithologists' Union, Quarterly field report, fall 1986 - Kent, Thomas H. (Thomas Hugh), 1934-et al (1986)
The report notes the cool, wet fall season, discusses the good migrations of the season and the unusually large number of sightings of rare water birds, mostly at Saylorville Lake. Included with the report are two letters from Carl J. Bendorf to Bruce Peterjohn. The letter dated December 15, 1986, explains the presence of typesetting marks on the included fall report manuscript and notes the interesting fall season in Iowa. The letter dated December 23, 1986, notes two late reports, of a King Eider and a Swainson's Hawk, and mentions winter sightings. Epson - sheet feed